Diwali : festival of lights - Singh, Rina, 1955- (Orca origins., 2016)
During Diwali, Hindus, Sikhs and Jains celebrate the legends and stories that describe the triumph of good over evil and justice over oppression. Critically acclaimed author Rina Singh explores her Indian roots as she tells the Diwali stories, which remind us that eventually light will prevail over darkness. Enriched by personal stories and spiced with festive recipes, Diwali: Festival of Lights brings to life the holiday's traditions, food and rituals and takes you on a journey to see how this festival is celebrated around the world! --Publisher's description.